Transformasi dan Manajemen Pendidikan Islam - Khoirotul Izzah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
Transformation is a transformation that can be said to be a total or complete change and covers all aspects until it becomes something new at all such as the change from a caterpillar to a butterfly.covering an organizational transformation program is more of a strategic decision and effort so closely related to corporate/organizational strategy. In addition, transformation must be carried out in an effort to support the realization of a vision and mission. The direction of the transformation of Islamic education management as a step change includes planning, organizing, mobilization and supervision through effective, efficient, and productive cooperation to achieve common goals. The transformation and innovation of Islamic religious education management can be interpreted as a total and complete change and cover all aspects until it becomes something new in the effort to make changes with the aim of obtaining better things in the field of Islamic education management.